2021
DOI: 10.31557/apjcp.2021.22.10.3219
|View full text |Cite
|
Sign up to set email alerts
|

p16INK4A Expression in Condyloma Acuminata Lesions Associated with High-Risk Human Papillomavirus Infection

Abstract: Objective: The objective of this study was to discover the possible correlation between p16INK4A expression and the LR/HR-HPV infection in condyloma acuminate (CA) lesions. Materials and Method: This cross-sectional study was conducted during January-December 2017 on 33 CA patients. The expression of p16 INK4A was detected by immunohistochemistry (IHC) staining. The positive interpretation was carried out by scoring which score 0 was negative,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 33 publications
0
8
0
2
Order By: Relevance
“…There are 12 subtypes of MAGE A which share a conserved MAGE homology domain (MHD) [11]. The subtypes including MAGE A1, MAGE A2, MAGE A3, MAGE A4, MAGE A5, MAGE A6, MAGE A7 (pesudo gene), MAGE A8, MAGE A9, MAGE A10, MAGE A11, MAGE A12 [11,12]. Expression of these genes are usually restricted to germline cells such as the ovary, testis, placenta, and fetus that may relate to germ cell development [10,11,13].…”
Section: Expression Of Mage A1 To Mage A10 In the Forceps Biopsy And ...mentioning
confidence: 99%
See 2 more Smart Citations
“…There are 12 subtypes of MAGE A which share a conserved MAGE homology domain (MHD) [11]. The subtypes including MAGE A1, MAGE A2, MAGE A3, MAGE A4, MAGE A5, MAGE A6, MAGE A7 (pesudo gene), MAGE A8, MAGE A9, MAGE A10, MAGE A11, MAGE A12 [11,12]. Expression of these genes are usually restricted to germline cells such as the ovary, testis, placenta, and fetus that may relate to germ cell development [10,11,13].…”
Section: Expression Of Mage A1 To Mage A10 In the Forceps Biopsy And ...mentioning
confidence: 99%
“…Moreover, in FB samples that did not contain malignant cells showed that MAGE A5 was found positive in 6/18 (33.3 %) specimens, MAGE A9 was 4/18 (22.2 %) specimens, MAGE A1 was 3/18 (16.7 %) specimens, MAGE A3 and MAGE A8 were 2/18 (11.1 %) specimens incubation at 98 o C for 5 minutes. The resulting cDNA was stored at 40 o C or 20 o C [12,17]. To monitor the quality and integrity of the cDNA, RT PCR was conducted to detect the housekeeping gene, i.e., the glyceraldehyde-3phosphate dehydrogenase (GAPDH).…”
Section: Sample Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main histopathological characteristics of condyloma include acanthosis, papillomatosis, hyperkeratosis, parakeratosis and koilocytosis and mononuclear inflammatory infiltration in microscopic examination ( 20 – 24 ). Koilocytotic atypia considered as pathognomonic criteria for productive HPV infected squamous epithelium with perinuclear cytoplasmic clear zone and condensed nuclei ( 25 , 26 ). Cytoplasmic vacuoles and relatively enlarged nucleus is the predominant morphological feature ( 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…Adenosquamous carcinoma is defined as a tumor having both glandular and squamous cell differentiation, with each component visible on hematoxylin-eosin without special histochemical stains (1-4) Adenosquamous carcinoma of the cervix accounts for approximately 4 % of all cervical cancer. Like both squamous cell carcinoma and adenocarcinoma, the mean age when the tumor develops is 57 years, although in individual cases it may occur in young women (2,(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%